2013
DOI: 10.1155/2013/268708
|View full text |Cite
|
Sign up to set email alerts
|

Material Handling Equipment Selection Using Weighted Utility Additive Theory

Abstract: �etter utilization of manpower, providing product �exibility, increasing productivity, decreasing lead time, reduction in handling cost, increased efficiency of material �ow, and enhancement of production process are some of the most important issues in�uencing material handling (MH) equipment selection decision. As a wide variety of MH equipment is available today, selection of the proper equipment for a designed manufacturing system is a complicated task. Selection of suitable MH equipment for a typical hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
0
39
2
Order By: Relevance
“…It was found that the ranking obtained by CODAS, EDAS, WASPAS and MOORA methods were the same and in agreement with other MCDM methods like TOPSIS and ELECTRE. Karande and Chakraborty (2013) solved the same problem with ELECTRE and obtained the rank as A3>A4>A2>A1. Rao (2007) solved the problem using TOPSIS method and got the rank A3>A4>A2>A1.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the ranking obtained by CODAS, EDAS, WASPAS and MOORA methods were the same and in agreement with other MCDM methods like TOPSIS and ELECTRE. Karande and Chakraborty (2013) solved the same problem with ELECTRE and obtained the rank as A3>A4>A2>A1. Rao (2007) solved the problem using TOPSIS method and got the rank A3>A4>A2>A1.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Rao (2007) solved the problem and calculated the preference index for the same four conveyors using simple additive weighting, weighted product method, analytical hierarchy process, graph theory and matrix approach, technique for order performance by similarity to ideal solution (TOPSIS) and modified TOPSIS. Karande and Chakraborty (2013) solved the same problem using weighted utility additive (WUTA) method, VIse Kriterijumska Optimizacija kompromisno Resenje (VIKOR), Preference Ranking Organization method for enrichment evaluation (PROMETHEE), ELECTRE methods and compared the ranking obtained by different methods. Table 1 …”
Section: Moora Methods Was Introduced By Brauers In 2004mentioning
confidence: 99%
“…Generally, the materials handling component makes up 30-75% of a mine's operating cost (Karande and Chakraborty, 2013). In Central Africa, as in many developing regions, mineral projects have to invest substantially in establishing transport infrastructure.…”
mentioning
confidence: 99%
“…Karande and Chakraborty (2013, p. 2) list criteria such as 'better utilization of manpower, providing product flexibility, increasing productivity, decreasing lead time, reduction in handling cost, increased efficiency of material flow, and enhancement of production process' as just some of the criteria to consider. They emphasize that the decision-making process should use a multi-criteria analysis approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation